(untitled) (Web of Teachers: Inderscience Research, 2025)
Topraq Qala, located in the Ellikqala region of Karakalpakstan, Uzbekistan, is one of the most significant architectural and archaeological monuments of ancient Khorezm. Serving as the capital of the Khorezmshahs’ state during the 1st–4th centuries CE, it stands today as a vital cultural heritage site. However, centuries of exposure to natural and anthropogenic factors have severely damaged its structures. This paper examines the historical significance of Topraq Qala, analyzes current problems in technical condition assessment, explores preservation and conservation measures, and discusses restoration strategies and future prospects. The research emphasizes the importance of scientific approaches, international cooperation, and sustainable financing in safeguarding this unique cultural monument.